The Women's Guide to Surviving Graduate School. - Rittner, Barbara (Graduate survival skills., 1997)
Written by women for women, this book provides practical information and advice on graduate schools in the United States and Canada. Basic information is provided for each graduate school about selection, applications and acceptance processes, likely cost and funding sources. The authors also provide valuable advice on how to determine the best methods for planning a course of study and selecting programmes.